In vivo vocal fold augmentation using an injectable polyethylene glycol hydrogel based on click chemistry - Kwon, Soonmin; Choi, Hyunsu; Park, Changhee; Choi, Sangkee; Kim, Eunha; Kim, Sung Won; Kim, Choung Soo; Koo, Heebeom (Biomaterials Science, 2021)
It is important to focus on urgent needs in clinics and develop optimal materials. For successful augmentation of vocal folds, the ideal filler should be injectable through a syringe, and should stably maintain its volume for a long time without toxicity. To achieve these criteria, a click chemistry-based PEG (polyethylene glycol) hydrogel was developed and applied for vocal fold augmentation in vivo. The PEG hydrogel enables fast gelation in vivo after injection and provides long-term stability. Azide- and dibenzocyclooctyne (DBCO)-modified 4-arm PEG were cross-linked by chemical conjugation via click chemistry and yielded gelation within several minutes. After subcutaneous injection into mice and rats, the PEG hydrogel showed higher stability after 1 month compared to the traditionally used calcium hydroxyapatite-carboxymethyl cellulose (CaHA-CMC) filler. In rabbit models with vocal fold paralysis, the PEG hydrogel stably fixed the paralyzed vocal fold in 4 months and minimized the glottic gap. It was an improved therapeutic result compared to CaHA-CMC, demonstrating the potential of a click chemistry-based PEG hydrogel for vocal fold therapy.
Keywords: Calcium hydroxyapatite; Carboxy-methyl cellulose; Click chemistry; Long term stability; Optimal materials; Peg hydrogel; Rabbit models; Vocal folds; Animals; Biocompatible Materials; Click Chemistry; Hydrogels; Mice; Polyethylene Glycols; Rabbits; Rats; Vocal Cords